Reversión sexual de tilapia roja oreochromis niloticus utilizando dos tipos de androgenos comerciales y un testigo andriol y proviron - Almeida Caiche, Julio William (2014)
This research was conducted in the Laboratory of Mariculture, Faculty of Agricultural Sciences located at the Farm St. Agnes belonging to the Technical University of Machala Km 51/2vía to Passage , its geographical coordinates are: Latitude the 5th 3'16 " , Length 79th 57 ' and a height of 6.5 m. The laboratory was GABATY provider Tilapia fingerlings, located at Finch JENNY DELIA, located in Canton Taura, belonging to the province of Guayas. Fingerlings in the laboratory are carried out its acclimation to count to then be distributed in number of two hundred per treatment. The average weight was nine milligrams, four-millimeter size, with an age of four days from hatching. Sowing was done on 20 August and the beginning of sex reversal occurred from August 22 2013. The balanced provided the fry considering biomass supplied, distributed in six daily. Seeded fish, which was in a total of 200, was considered significant sample of 50% of the total planted per treatment. Observing the genital poreshiso manually using methylene blue, separating as sex identification. Proviron treatments, Andriol and Witness, received the same dose of food frequencies and by biomass. The percentages of male tilapia achieved by applying Proviron were 89.7 %, which was used Andriol was obtained 59.3 % of males and in the Witness was obtained 54.8 % of males. The results in this research show that the hormone Proviron , was more effective at the time to exert its effect during the sexual induction process , taking into account that applying Andriol and supply food to the fish that made the witness, was strictly under biotic the same conditions with the same supply frequency.